Organizational Work-life Balance Policies Toward Women and Their Reflection in Employee Commitment and Labor Market Image: A Social Exchange Theory Approach - Md. Amanullah; Dip Das; Motaleb Bhuiyan (Journal of Risk Analysis and Crisis Response (JRACR))
Balancing working life and personal life is quite challenging, especially for women who must play diverse roles at a time. Family obligations and the nature of work also influence the intensity of work-life conflict. A well-articulated human resource policy may not wipe out the role conflict but can minimize it prudently. This study is designed to examine whether the existing WLB policies of private commercial banks in Bangladesh are designated enough to influence the female bankers’ level of commitment and their attitude toward job market. Based on the social exchange theory, this study assesses the experience of 450 mid-career bankers deploying the PLS-SEM approach. The results infer that mid-level female bankers show a satisfactory level of commitment to their employment and a positive attitude toward the labor market despite the challenging job requirements. Additionally, their affection toward the banking career brings significantly positive results in influencing their commitment and labor market perception. The study also explored moderating impact and observed that the career commitment substantially moderates the WLB and employee commitment relationship. As women have strong ties to family responsibilities in the cultural context of Bangladesh, understanding the perceived consequences of WLB is essential to formulating effective policies. Besides enriching theoretical understanding, the findings will help the managers and policymakers to understand the value of offering effective policies for female bankers to balance their work and life.